EFEKTIVITAS TEKNIK BUZZ GROUP UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Siti Khoirul Larasari; Deasy Yunika Khairun; Bangun Yoga Wibowo (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2022)
This study aims to determine the effectiveness of the buzz group technique to increase students learning motivation. This is expected to contribute to being able to provide appropriate treatment so that students can increase their learning motivation. This research was conducted at SMA Nur El Falah with a target population of class XI SMA for the academic year 2021/2022. The population requirements determined are students of class XI SMA Nur El Falah for the academic year 2021/2022 who are indicated to have low learning motivation and are committed or willing to take treatment. The number of respondents obtained as many as 8 students with the purposive sampling technique which was revealed from the distribution of learning motivation questionnaires consisting of aspects of intrinsic motivation and extrinsic motivation with a reliability of 0.866. The method used is a pre-experiment with a one-group pretest-posttest design. The average value of the pre-test obtained by the experimental group was 48.80%. After being given treatment, it increased by 28.5% to 77.30%. In the experimental group, the results of the non-parametric difference test with the Wilcoxon formula showed sig. (2- tailed ) 0.011 significance level [Î± = 0.05] then Sig. (2- tailed ) > 0.05 which means the effectiveness of the buzz group technique to increase students learning motivation.